Refractive accuracy after intraocular lens implantation in pediatric cataract - Long, Tan (International Journal of Ophthalmology Press, 2012)
AIM: To analyze the factors that influence the prediction error (PE) after intraocular lens (IOL) implantation in pediatric cataract. METHODS: The medical records of cataract patients of no more than 14 years old who had primary IOL implantation were reviewed from 2006 to 2010. The PE, absolute value of PE (APE), and predictability between in different axial length, mean corneal curvature, corneal astigmatism, and age at the surgery were analyzed. RESULTS: Seventy-five children (119 eyes) were included, with a mean age of (5.09±2.54) years. At the follow-up of (1.19±0.69) months, the mean postoperative PE was (-0.22±1.12) D, and APE was (0.87±0.73)D. The PE in eyes with an axial length >20mm but ≤22mm were significantly under-corrected than that in eyes with longer axis, and the APE in eyes with an axial length ≤20mm was more obvious compared with the others. The correlations between PE and axial length, as well as corneal astigmatism, and between APE and axial length were significant. The predictability was significantly poorer in the eyes with an axial length ≤20mm than the others. CONCLUSION: The axial length is closely related with the PE after IOL implantation in pediatric cataract patients, especially when it is ≤20mm, PE is more significant. The formula that is more suitable to very short axial length should be explored.